2013
DOI: 10.4172/2161-0509.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition and Associated Factors among Children Age 6-59 Months at Lalibela Town Administration, North WolloZone, Anrs, Northern Ethiopia

Abstract: Background: Children are most vulnerable to malnutrition in developing countries because of low dietary intakes, lack of appropriate care, and inequitable distribution of food within the household. Malnutrition remains one of the most common causes of morbidity and mortality among children throughout the world. Malnutrition In Ethiopia, in the form of stunting, underweight and wasting were identified as 44%, 29% and 10% and Amhara National region state 52%, 33.4% and 9.9%, respectively in children under five. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
33
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 12 publications
18
33
2
1
Order By: Relevance
“…20 In our study, the most prevalent causes of malnutrition among malnourished children were helminthes and parasitic infestation, followed by gastroenteritis and improper weaning. The current study revealed that these causes were statistically associated with wasting, stunting, and underweight, these results were agreed with studies concluded in Alexandria, Malaysia, and The Peruvian Amazon that high socioeconomic and good environmental conditions were the most important factors associated with the lower prevalence of malnutrition.…”
Section: Discussionmentioning
confidence: 57%
“…20 In our study, the most prevalent causes of malnutrition among malnourished children were helminthes and parasitic infestation, followed by gastroenteritis and improper weaning. The current study revealed that these causes were statistically associated with wasting, stunting, and underweight, these results were agreed with studies concluded in Alexandria, Malaysia, and The Peruvian Amazon that high socioeconomic and good environmental conditions were the most important factors associated with the lower prevalence of malnutrition.…”
Section: Discussionmentioning
confidence: 57%
“…This result was similar to EDHS [4] and other studies done in Ethiopia 41%, 35% respectively. The cause of this discrepancy in sex is no well established in the literature, but it is believed that boys are more influenced by environmental stress than girls [18]. Child health and care practice in this study 84.5% of children feed colostrums 15.5 % of children were not depilated the first milk/colostrums.…”
Section: Stuntingmentioning
confidence: 85%
“…It has been responsible, directly or indirectly, for 60% of the 10.9 million deaths annually among children under five and two-thirds of these deaths, which are often associated with inappropriate feeding practices [1,2]. Children are most vulnerable to malnutrition in developing countries because of low dietary intakes, lack of appropriate care, and inequitable distribution of food within the household [3,4]. Over one third of under-five mortality is caused by malnutrition related to inappropriate complementary feeding.…”
Section: Introductionmentioning
confidence: 99%